Eccrine angiomatous hamartoma - Dąbrowska, Natalia; Czuwara, Joanna; Warszawik-Hendzel, Olga; Olszewska, Małgorzata; Rudnicka, Lidia (Dermatology Review/Przegląd Dermatologiczny, 2023)
Eccrine angiomatous hamartoma is a rare, benign skin tumor typically occurring on the hands and feet. It is usually congenital in origin but, less commonly, it may also appear later in life. Eccrine angiomatous hamartoma may appear in various colours and forms: a macule, papule, plaque or nodule, resembling angioma. Associated symptoms include hyperhidrosis within the lesion. Definitive diagnosis requires histopathological examination. The most characteristic microscopic features include eccrine glands hyperplasia, and vascular proliferation and dilatation. In most instances, eccrine angiomatous hamartoma does not necessitate treatment; however, surgical removal of the lesion might be recommended in specific cases. Other treatment options include botulinum toxin injections and laser therapy.